Method for improving efficiency of sodium ion negative electrode dry pulping process
Through the dry preparation process and the use of modified carbon nanotubes, the problems of uneven dispersion of materials and high resistivity in traditional wet processes are solved, the stability and conductivity of the negative electrode slurry of sodium ion battery are improved, and the battery performance is improved.
Patent Information
- Application Number
- CN202510000750.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-18
AI Technical Summary
The traditional wet method of preparing the negative electrode slurry of sodium ion batteries takes a long time, and the material is unevenly dispersed, resulting in poor slurry stability and high resistivity of the electrode sheet, which affects battery performance and consistency.
The dry preparation process is adopted, and the uniformity and conductivity of the material are improved through the steps of powder mixing, kneading, high-speed dispersion, low-speed dispersion and vacuum defoaming.
It improves the stability and conductivity of the sodium ion negative electrode slurry, reduces the peel strength and resistivity of the electrode plate, and improves the overall performance of the sodium ion battery.
Smart Images

Figure CN119852298A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a method for improving the efficiency of a sodium ion negative electrode dry pulping process. Background Art
[0002] As the global energy transition accelerates, traditional lithium-ion batteries are facing increasingly prominent challenges in raw material supply, high cost, and technical development bottlenecks. Sodium resources are abundant and widely distributed, and the cost is low. Compared with lithium-ion batteries, sodium-ion batteries show broad market prospects in application scenarios such as large-scale energy storage.
[0003] The negative electrode material is one of the key factors affecting the performance of sodium-ion batteries. Currently, the graphite negative electrode material commonly used in lithium-ion batteries cannot be used in sodium-ion batteries, and disordered soft and hard carbon materials have become the preferred negative electrode materials for sodium-ion batteries at this stage. However, due to their own characteristics, they have poor dispersion effects in water, resulting in poor slurry uniformity and stability. In particular, the traditional wet method for preparing negative electrode slurry for sodium-ion batteries is generally time-consuming, and the negative electrode active materials and conductive agents are prone to uneven dispersion, resulting in particle agglomeration, slurry sedimentation, large viscosity changes, difficulty in screening, poor slurry stability, and high electrode resistivity, which affect the performance and consistency of the battery.
[0004] The dry preparation process has significant advantages in improving production efficiency and improving slurry performance. It can make the negative electrode active materials, conductive agents and other components more evenly mixed by precisely controlling the ratio of raw materials, stirring speed, stirring time, solid content, solvent dosage and other parameters, and using special dispersants, wetting agents and modifying materials, thereby improving the stability and consistency of the slurry, thereby improving the overall performance of sodium-ion batteries and promoting the industrialization of sodium-ion batteries. Summary of the invention
[0005] The purpose of the present invention is to provide a method for improving the efficiency of the dry pulping process of sodium ion negative electrode. The stability of the sodium ion negative electrode slurry obtained by the method is improved, and the peeling strength and resistivity of the electrode sheet are reduced, thereby improving the overall performance of the sodium ion battery and having significant industrial application value.
[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: A method for improving the efficiency of a sodium ion negative electrode dry pulping process, comprising: The negative electrode main material, rigid binder and conductive agent are mixed into powder form, and then deionized water and dispersant are added for kneading, a conductive additive is added for high-speed dispersion, an elastic binder is added for low-speed dispersion, and vacuum degassing is performed to obtain a negative electrode slurry.
[0007] Preferably, the negative electrode main material is hard carbon, the rigid binder is CMC, and the conductive agent is SP; the mass ratio of the negative electrode main material, the rigid binder and the conductive agent is 18.86-943:0.3-15:0.14-7.
[0008] Preferably, the conductive additive comprises carbon nanotubes or modified carbon nanotubes; the modified carbon nanotubes have morpholine groups, pyridine groups and polyethylene glycol groups.
[0009] Preferably, the dispersant is NMP, and the mass ratio of the negative electrode main material to the dispersant is 18.86-943:0.1886-9.43.
[0010] Preferably, the mass ratio of the negative electrode main material to the conductive additive is 18.86-943:0.1-5.
[0011] Preferably, the elastic binder is SBR, and the mass ratio of the negative electrode main material to the elastic binder is 18.86-943:0.6-30.
[0012] Preferably, the modified carbon nanotubes are obtained by modifying carboxylated carbon nanotubes with HEO, HPMA and PEG. The present invention adopts the modification process of using HEO and HPMA to act on carbon nanotubes, which can react with EDC and NHS to form active esters, provide more grafting sites for carbon nanotubes, enhance the interaction between carbon nanotubes and polymers, and form a stable carbon nanotube-polymer composite structure. The modified carbon nanotubes thus formed can improve the interface interaction with other components such as hard carbon, form a more stable network structure, provide more conductive paths, effectively reduce the resistivity of sodium ion negative electrode slurry, and ultimately improve the overall performance of sodium ion negative electrode slurry.
[0013] Preferably, the mass ratio of HEO to carboxylated carbon nanotubes is 0.1-2:0.075-1.5; or, the mass ratio of HPMA to carboxylated carbon nanotubes is 0.075-1.5:0.075-1.5; or, the mass ratio of PEG to carboxylated carbon nanotubes is 0.125-2.5:0.075-1.5.
[0014] More preferably, GNO can be added during the synthesis of the modified carbon nanotubes, and the mass ratio of GNO to carboxylated carbon nanotubes is 0.1-1:0.1-1. The addition of GNO can form modified carbon nanotubes with good interfacial compatibility, which can enhance the interfacial interaction between carbon nanotubes and other materials, thereby improving the uniformity and stability of the overall slurry, while increasing the conductivity of the slurry, reducing the resistivity of the electrode sheet, and increasing the diffusion rate of sodium ions in the electrode material, thereby improving the performance of the battery.
[0015] The present invention provides a method for preparing carboxylated carbon nanotubes, comprising: The carbon nanotubes are dispersed in DMF, and ultrasonicated for 15-45 minutes to uniformly disperse the carbon nanotubes to obtain a carbon nanotube dispersion. Para-aminobenzoic acid is dissolved in deionized water to form a para-aminobenzoic acid solution. The carbon nanotube dispersion and the para-aminobenzoic acid solution are mixed, and the pH value is adjusted to 1.8-2.4. The mixture is heated to 55-65° C. under nitrogen protection for reaction for 6-18 hours, and then cooled to room temperature. The mixture is centrifuged and filtered, and the precipitate is washed with deionized water and dried at 35-45° C. for 12-36 hours to obtain carboxylated carbon nanotubes.
[0016] Preferably, the mass volume ratio of carbon nanotubes to DMF is 0.1-1 g:10-100 mL.
[0017] Preferably, the mass volume ratio of p-aminobenzoic acid to deionized water is 1-10g:10-100mL.
[0018] Preferably, the mass of the carbon nanotube dispersion is measured by the mass of the carbon nanotubes therein, the mass of the p-aminobenzoic acid solution is measured by the mass of the p-aminobenzoic acid therein, and the mass ratio of the carbon nanotube dispersion to the p-aminobenzoic acid solution is 0.1-5:0.4-20.
[0019] Preferably, the centrifugal speed is 6000-10000 rpm, and the duration is 10-20 min.
[0020] The present invention provides a method for preparing modified carbon nanotubes, comprising: Disperse the carboxylated carbon nanotubes in toluene, and perform ultrasonic treatment for 40-80 minutes to uniformly disperse the carboxylated carbon nanotubes to form a carboxylated carbon nanotube dispersion, dissolve HEO, HPMA and PEG in DMF to form a DMF mixed solution, add the DMF mixed solution to the carboxylated carbon nanotube dispersion to form a carboxylated carbon nanotube mixed solution, and add EDC and NHS. Heat to 65-75°C under nitrogen protection for reaction for 6-12 hours, then cool to room temperature, centrifuge and filter, wash the precipitate with deionized water, and dry at 45-55°C for 24-48 hours to obtain modified carbon nanotubes.
[0021] Preferably, the mass volume ratio of carboxylated carbon nanotubes to toluene is 0.75-1.5 g:25-250 mL.
[0022] Preferably, the mass volume ratio of HEO to DMF is 0.1-2 g:5-100 mL.
[0023] Preferably, the mass volume ratio of HPMA to DMF is 0.075-1.5 g:5-100 mL.
[0024] Preferably, the mass volume ratio of PEG to DMF is 0.125-2.5 g:5-100 mL.
[0025] Preferably, the volume of the DMF mixture is measured by the volume of DMF therein, the volume of the carboxylated carbon nanotube dispersion is measured by the volume of toluene therein, and the volume ratio of the DMF mixture to the carboxylated carbon nanotube dispersion is 5-100:12.5-250.
[0026] Preferably, the volume of the DMF mixed solution is measured by the volume of DMF therein, and the mass volume ratio of EDC to DMF mixed solution is 0.1-1g:10-100mL.
[0027] Preferably, the volume of the DMF mixture is measured by the volume of DMF therein, and the mass volume ratio of NHS to DMF mixture is 0.075-0.75 g:10-100 mL.
[0028] Preferably, the centrifugal speed is 6000-10000 rpm, and the duration is 10-20 min.
[0029] The present invention provides a method for preparing a sodium ion negative electrode slurry, comprising: The negative electrode main material, rigid binder and conductive agent are mixed into powder in proportion; deionized water and dispersant are added and kneaded; conductive additive and deionized water are added for high-speed dispersion; after cooling to room temperature, elastic binder is added for low-speed dispersion; deionized water is added to adjust the viscosity of the slurry to the coating viscosity window, and vacuum degassing is performed to obtain sodium ion negative electrode slurry.
[0030] Preferably, the main material of the negative electrode is hard carbon.
[0031] Preferably, the rigid binder is CMC, and the mass ratio of CMC to hard carbon is 0.3-15:18.86-943.
[0032] Preferably, the conductive agent is SP, and the mass ratio of SP to hard carbon is 0.14-7:18.86-943.
[0033] Preferably, during the powder mixing stage, the rotation speed is 30-40 rpm for revolution and 400-800 rpm for rotation, and the duration is 30-60 min.
[0034] Preferably, the dispersant is NMP, and the mass ratio of NMP to hard carbon is 18.86-943:0.1886-9.43.
[0035] Preferably, in the kneading stage, the mass ratio of deionized water to hard carbon is 4-200:18.86-943.
[0036] Preferably, the kneading stage includes preliminary kneading and deep kneading. The preliminary kneading speed is 10-20 rpm for revolution and 0 rpm for rotation, and the duration is 5-15 min. The deep kneading speed is 30-40 rpm for revolution and 0 rpm for rotation, and the duration is 30-60 min.
[0037] Preferably, the conductive additive is carbon nanotubes or modified carbon nanotubes, and the mass ratio of carbon nanotubes or modified carbon nanotubes to hard carbon is 0.1-5:18.86-943.
[0038] Preferably, in the high-speed dispersion stage, the mass ratio of deionized water to hard carbon is 3-150:18.86-943.
[0039] Preferably, in the high-speed dispersion stage, the rotation speed is 30-40 rpm for revolution and 1500-2000 rpm for rotation, and the duration is 30-60 min.
[0040] Preferably, the elastic binder is SBR, and the mass ratio of SBR to hard carbon is 0.6-30:18.86-943.
[0041] Preferably, in the low-speed dispersion stage, the rotation speed is 25-35 rpm for revolution and 200-600 rpm for rotation, and the duration is 15-45 minutes.
[0042] Preferably, the coating viscosity window is 1500-3000 cp.
[0043] Preferably, during the vacuum degassing stage, the rotation speed is 5-15 rpm for the revolution and 0 rpm for the rotation, and the duration is 15-45 min.
[0044] The present invention adds modified carbon nanotubes and the like as conductive additives to the negative electrode slurry, and after the carbon nanotubes are carboxylated, the carbon nanotubes are grafted and modified using HEO, HPMA and PEG, thereby having the following beneficial effects: the interface interaction between the modified carbon nanotubes and other components such as hard carbon is enhanced, and the formed structure is more stable; there are more conductive paths, the conductivity is enhanced, and the diffusion rate of sodium ions in the electrode material is increased. Therefore, the sodium ion negative electrode slurry obtained by the present invention has high stability, and the prepared sodium ion negative electrode sheet has high peeling strength and low resistivity, and has broad practical value and application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 Schematic diagram of the 600°C thermogravimetric analysis test results of the sodium ion negative electrode slurry.
[0046] Figure 2 Schematic diagram of the peel strength test results of the negative electrode sheet prepared with sodium ion negative electrode slurry.
[0047] Figure 3Schematic diagram of the resistivity test results of the negative electrode sheet prepared with sodium ion negative electrode slurry. DETAILED DESCRIPTION
[0048] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] The following first describes the concepts involved in the present application in conjunction with the accompanying drawings. It should be noted that the following description of each concept is only to make the content of the present application easier to understand, and does not limit the scope of protection of the present application; at the same time, the embodiments and features in the embodiments of the present application can be combined with each other in the absence of conflict. The present application will be described in detail with reference to the accompanying drawings and in conjunction with the embodiments.
[0050] The Chinese meanings of the abbreviations used in the present invention are shown in Table 1 below: Table 1 Abbreviations corresponding to Chinese meanings
[0051] Embodiment 1: The negative electrode main material, rigid binder and conductive agent are mixed in proportion at a revolution of 35 rpm and a rotation speed of 600 rpm for 45 minutes to form powders; deionized water and dispersant are added, and preliminary kneading is carried out at a revolution of 15 rpm and a rotation speed of 0 rpm for 10 minutes, and then deep kneading is carried out at a revolution of 35 rpm and a rotation speed of 0 rpm for 45 minutes; conductive additives and deionized water are added, and high-speed dispersion is carried out at a revolution of 35 rpm and a rotation speed of 1800 rpm for 45 minutes; after cooling to room temperature, an elastic binder is added, and low-speed dispersion is carried out at a revolution of 30 rpm and a rotation speed of 400 rpm for 30 minutes; deionized water is added to adjust the viscosity of the slurry to a coating viscosity window of 2000 cp, and sodium ion negative electrode slurry is obtained by vacuum degassing at a revolution of 10 rpm and a rotation speed of 0 rpm for 30 minutes. The main material of the negative electrode is hard carbon; the rigid binder is CMC, and the mass ratio of CMC to hard carbon is 1.5:94.3; the conductive agent is SP, and the mass ratio of SP to hard carbon is 0.7:94.3; the dispersant is NMP, and the mass ratio of NMP to hard carbon is 0.943:94.3; in the kneading stage, the mass ratio of deionized water to hard carbon is 20:94.3; the conductive additive is carbon nanotubes, and the mass ratio of carbon nanotubes to hard carbon is 0.5:94.3; in the high-speed dispersion stage, the mass ratio of deionized water to hard carbon is 15:94.3; the elastic binder is SBR, and the mass ratio of SBR to hard carbon is 3:94.3.
[0052] Example 2: Compared with Example 1, the only difference between this example and Example 1 is that the conductive additive is modified carbon nanotubes.
[0053] Preparation of carboxylated carbon nanotubes: disperse carbon nanotubes in DMF, ultrasonicate for 30 minutes to uniformly disperse carbon nanotubes to obtain carbon nanotube dispersion, dissolve p-aminobenzoic acid in deionized water to form p-aminobenzoic acid solution; mix carbon nanotube dispersion with p-aminobenzoic acid solution, adjust pH value to 2, heat to 60°C under nitrogen protection for 12 hours, cool to room temperature, centrifuge at 8000rpm for 15 minutes, filter, wash precipitate with deionized water, dry at 40°C for 24 hours, and obtain carboxylated carbon nanotubes. The mass volume ratio of carbon nanotubes to DMF is 0.5g:50mL; the mass volume ratio of p-aminobenzoic acid to deionized water is 2g:20mL; the mass of carbon nanotube dispersion is measured by the mass of carbon nanotubes therein, the mass of p-aminobenzoic acid solution is measured by the mass of p-aminobenzoic acid therein, and the mass ratio of carbon nanotube dispersion to p-aminobenzoic acid solution is 0.5:2.
[0054] Preparation of modified carbon nanotubes: Disperse carboxylated carbon nanotubes in toluene, ultrasonicate for 60 minutes to uniformly disperse the carboxylated carbon nanotubes to obtain a carboxylated carbon nanotube dispersion, dissolve HEO, HPMA and PEG in DMF to obtain a DMF mixed solution, add the DMF mixed solution to the carboxylated carbon nanotube dispersion, and add EDC and NHS. Heat to 70°C under nitrogen protection for 8 hours, then cool to room temperature, centrifuge at 10,000 rpm for 20 minutes, filter, wash the precipitate with deionized water, and dry at 50°C for 36 hours to obtain modified carbon nanotubes. The mass ratio of carboxylated carbon nanotubes to toluene is 0.3g:50mL; the mass volume ratio of HEO to DMF is 0.4g:20mL; the mass volume ratio of HPMA to DMF is 0.3g:20mL; the mass volume ratio of PEG to DMF is 0.5:20mL; the volume of the DMF mixed solution is measured by the volume of DMF therein, the volume of the carboxylated carbon nanotube dispersion is measured by the volume of toluene therein, the volume ratio of the DMF mixed solution to the carboxylated carbon nanotube dispersion is 20:50, the mass volume ratio of the EDC to DMF mixed solution is 0.2g:20mL, and the mass volume ratio of the NHS to DMF mixed solution is 0.15g:20mL.
[0055] Example 3: Compared with Example 2, the difference between this example is the preparation of modified carbon nanotubes.
[0056] Preparation of modified carbon nanotubes: Disperse carboxylated carbon nanotubes in toluene, ultrasonicate for 60 minutes to uniformly disperse the carboxylated carbon nanotubes to obtain a carboxylated carbon nanotube dispersion, dissolve HEO, HPMA and PEG in DMF to obtain a DMF mixed solution, add the DMF mixed solution to the carboxylated carbon nanotube dispersion, and add EDC and NHS. Heat to 70°C under nitrogen protection for 8 hours, then cool to room temperature, centrifuge at 10,000 rpm for 20 minutes, filter, wash the precipitate with deionized water, and dry at 50°C for 36 hours to obtain modified carbon nanotubes. The mass ratio of carboxylated carbon nanotubes to toluene is 0.3g:50mL; the mass volume ratio of HEO to DMF is 0.2g:20mL; the mass volume ratio of HPMA to DMF is 0.6g:20mL; the mass volume ratio of PEG to DMF is 0.5:20mL; the volume of the DMF mixed solution is measured by the volume of DMF therein, the volume of the carboxylated carbon nanotube dispersion is measured by the volume of toluene therein, the volume ratio of the DMF mixed solution to the carboxylated carbon nanotube dispersion is 20:50, the mass volume ratio of the EDC to DMF mixed solution is 0.2g:20mL, and the mass volume ratio of the NHS to DMF mixed solution is 0.15g:20mL.
[0057] Example 4: Compared with Example 2, the difference between this example is the preparation of modified carbon nanotubes.
[0058] Preparation of modified carbon nanotubes: Disperse carboxylated carbon nanotubes in toluene, ultrasonicate for 60 minutes to evenly disperse the carboxylated carbon nanotubes to obtain a carboxylated carbon nanotube dispersion, dissolve HEO, HPMA, GNO and PEG in DMF to obtain a DMF mixed solution, add the DMF mixed solution to the carboxylated carbon nanotube dispersion, and add EDC and NHS. Heat to 70°C under nitrogen protection for 8 hours, then cool to room temperature, centrifuge at 10,000 rpm for 20 minutes, filter, wash the precipitate with deionized water, and dry at 50°C for 36 hours to obtain modified carbon nanotubes. The mass ratio of carboxylated carbon nanotubes to toluene is 0.3g:50mL; the mass volume ratio of HEO to DMF is 0.4g:20mL; the mass volume ratio of HPMA to DMF is 0.3g:20mL; the mass volume ratio of GNO to DMF is 0.3g:20mL; the mass volume ratio of PEG to DMF is 0.5:20mL, the volume of the DMF mixture is measured by the volume of DMF therein, the volume of the carboxylated carbon nanotube dispersion is measured by the volume of toluene therein, and the volume ratio of the DMF mixture to the carboxylated carbon nanotube dispersion is 20:50; the mass volume ratio of the EDC to DMF mixture is 0.2g:20mL, and the mass volume ratio of the NHS to DMF mixture is 0.15g:20mL.
[0059] Example 5: Compared with Example 2, the difference between this example is the preparation of modified carbon nanotubes.
[0060] Preparation of modified carbon nanotubes: Disperse carboxylated carbon nanotubes in toluene, ultrasonicate for 60 minutes to evenly disperse the carboxylated carbon nanotubes to obtain a carboxylated carbon nanotube dispersion, dissolve HEO, HPMA, GNO and PEG in DMF to obtain a DMF mixed solution, add the DMF mixed solution to the carboxylated carbon nanotube dispersion, and add EDC and NHS. Heat to 70°C under nitrogen protection for 8 hours, then cool to room temperature, centrifuge at 10,000 rpm for 20 minutes, filter, wash the precipitate with deionized water, and dry at 50°C for 36 hours to obtain modified carbon nanotubes. The mass ratio of carboxylated carbon nanotubes to toluene is 0.3g:50mL; the mass volume ratio of HEO to DMF is 0.4g:20mL; the mass volume ratio of HPMA to DMF is 0.3g:20mL; the mass volume ratio of GNO to DMF is 0.6g:20mL; the mass volume ratio of PEG to DMF is 0.5:20mL; the volume of the DMF mixed solution is measured by the volume of DMF therein, the volume of the carboxylated carbon nanotube dispersion is measured by the volume of toluene therein, the volume ratio of the DMF mixed solution to the carboxylated carbon nanotube dispersion is 20:50, the mass volume ratio of the EDC to DMF mixed solution is 0.2g:20mL, and the mass volume ratio of the NHS to DMF mixed solution is 0.15g:20mL.
[0061] Comparative Example 1: The only difference between this comparative example and Example 2 is that HEO is not used in the preparation of modified carbon nanotubes.
[0062] Comparative Example 2: The only difference between this comparative example and Example 2 is that HPMA is not used in the preparation of modified carbon nanotubes.
[0063] 1. Thermogravimetric analysis test Test sample: sodium ion negative electrode slurry prepared by the methods of each embodiment and comparative example.
[0064] Test method: Place 10 mg of sodium ion negative electrode slurry in the sample crucible of the thermogravimetric analyzer, turn on the thermogravimetric analyzer, and heat it from room temperature to 600°C at a heating rate of 20°C / min under nitrogen protection, and record the data of the sample mass change with temperature monitored by the thermogravimetric analyzer.
[0065] The 600°C thermogravimetric analysis test results of the sodium ion negative electrode slurry prepared by the present invention are as follows: Figure 1As shown, the final residual mass of Experimental Example 1 is about 14%, the final residual mass of Experimental Example 2 is about 33%, the final residual mass of Experimental Example 3 is about 34%, the final residual mass of Experimental Example 4 is about 38%, and the final residual mass of Experimental Example 5 is about 41%. It can be seen from Example 1 to Example 5 that in the presence of modified carbon nanotubes, the mass loss rate is greatly reduced, proving that the modified carbon nanotubes have a great optimization effect on the stability of the negative electrode slurry. In the case of changes in the composition of the modified carbon nanotubes, due to the interaction between GNO and components such as the binder, the mass loss rate is lower than that of Example 2 and Example 3, and the change in the proportion of the modified carbon nanotube components leads to a reduction in the mass loss rate. Due to the lack of HEO modification, the carbon nanotubes and the binder are poorly bonded in Comparative Example 1, and the final residual mass is about 26%. The final residual mass of Comparative Example 2 is about 25%, because the carbon nanotubes are not effectively modified and the hard carbon structure cannot be stabilized, and the thermal stability of the carbon nanotubes is not optimized. This further illustrates that the two modifiers, HEO and HPMA, together constitute the key factors for maintaining the thermal stability structure of the material, and their absence significantly affects the decomposition process of each component of the material at high temperature.
[0066] 2. Peel strength test Test sample: sodium ion negative electrode slurry prepared by the methods of each embodiment and comparative example.
[0067] Test method: Apply the sodium ion negative electrode slurry to the copper foil current collector with a thickness of 100μm and a width of 5cm, and dry it at 80℃ for 4h to obtain the negative electrode. Use an electronic tensile testing machine to clamp the electrode and one end of the bonding material respectively, and place the bonding part between the two clamps and align them in a straight line. Record the change in the tensile force value and calculate it according to the peel strength (N / m) = peel force (N) / bonding width (m).
[0068] The peel strength test results of the negative electrode sheet prepared by the sodium ion negative electrode slurry prepared by the present invention are as follows: Figure 2As shown, the peel strength of Example 1 is 5.5 N / m, the peel strength of Example 2 is 7.1 N / m, the peel strength of Example 3 is 7.2 N / m, the peel strength of Example 4 is 7.5 N / m, and the peel strength of Example 5 is 8.0 N / m. It can be seen from Example 1 to Example 5 that in the presence of modified carbon nanotubes, the modified carbon nanotubes can play a role of reinforcement and connection in the pole piece structure, and form a more stable network structure with hard carbon, binder SBR, etc., especially when glycerophosphate-N-oleoylethanolamine is added, it can effectively enhance the bonding force between the pole piece and the bonding material. The addition of glycerophosphate-N-oleoylethanolamine further optimizes the interfacial interaction, enhances the bonding effect, and thus improves the peel strength. Due to the change in the composition ratio of the modified carbon nanotubes in Example 3 and Example 5, the peel strength is slightly reduced, but it is still maintained at a high level. HEO was not used in Comparative Example 1, and the peel strength dropped to 5.6 N / m compared with Example 2. This fully demonstrates that HEO plays a key role in improving the bonding ability of carbon nanotubes with other components during the preparation of modified carbon nanotubes. Its absence destroys the integrity of the pole piece structure, greatly weakening the bonding force between the pole piece and the bonding material. In Comparative Example 2, HEO is missing, and the peel strength is only 5.8N / m, which is also significantly lower than that of Example 2, proving the importance of HPMA in maintaining the stability of the pole piece structure and improving the peel strength. It shows that these two modifiers together constitute an important basis for enhancing the peel strength of the pole piece. The lack of them will lead to a loose pole piece structure, which is very easy to peel off when subjected to external forces.
[0069] 3. Electrode resistivity test Test sample: sodium ion negative electrode slurry prepared by the methods of each embodiment and comparative example.
[0070] Test method: The sodium ion negative electrode slurry was coated on a copper foil current collector with a thickness of 100 μm and a width of 5 cm, and dried at 80°C for 4 hours to obtain a negative electrode sheet. The edges and surface were polished with 1000-grit sandpaper, then cleaned with anhydrous ethanol and dried at 80°C for 60 minutes, and the resistivity was measured and calculated using a resistivity tester.
[0071] The resistivity test results of the negative electrode sheet prepared by the sodium ion negative electrode slurry prepared by the present invention are as follows: Figure 3As shown, the pole piece resistivity of Example 1 is 237mΩ・cm, the pole piece resistivity of Example 2 is 27mΩ・cm, the pole piece resistivity of Example 3 is 30mΩ・cm, the pole piece resistivity of Example 4 is 19mΩ・cm, and the pole piece resistivity of Example 5 is 23mΩ・cm. It can be seen from Example 1 to Example 5 that the introduction of modified carbon nanotubes provides a good conductive path for the pole piece and effectively reduces the resistivity. The glycerophospho-N-oleoylethanolamine added in Examples 4 and 5 further promotes electron conduction, optimizes the conductive network, and further reduces the resistivity. Due to the change in the composition of the modified carbon nanotubes in Examples 3 and 5, the resistivity is slightly increased compared with Examples 2 and 4. HEO was not used in Comparative Example 1, and the pole piece resistivity increased to 143mΩ・cm. This shows that HEO plays a key role in improving the conductivity of carbon nanotubes and thus reducing the pole piece resistivity during the modification process. Its absence leads to poor modification of carbon nanotubes and affects the construction of the conductive path. In Comparative Example 2, HPMA is missing, and the electrode sheet resistivity is 134 mΩ cm, which is significantly higher than that in Example 1. This proves that the two modifiers are essential for forming an efficient conductive network and reducing the electrode sheet resistivity. The lack of them will greatly reduce the conductive performance of the electrode sheet and cannot meet the requirements of the negative electrode of the sodium ion battery for good conductive performance.
[0072] The embodiments and / or implementation methods described above are only used to illustrate the preferred embodiments and / or implementation methods for realizing the technology of the present invention, and are not intended to limit the implementation methods of the technology of the present invention in any form. Any technical personnel in this field may make slight changes or modifications to other equivalent embodiments without departing from the scope of the technical means disclosed in the content of the present invention, but they should still be regarded as technologies or embodiments that are essentially the same as the present invention.
[0073] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and its core ideas of this application. The above is only the preferred implementation method of this application. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of this application, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the invention to other occasions without improvement, should be regarded as the scope of protection of this application.
Claims
1. A method for improving the efficiency of a sodium ion negative electrode dry pulping process, comprising: The negative electrode main material, rigid binder and conductive agent are powdered and mixed, and then deionized water and dispersant are added for kneading, a conductive additive is added for high-speed dispersion, an elastic binder is added for low-speed dispersion, and vacuum degassing is performed to obtain a negative electrode slurry; the negative electrode main material is hard carbon, the rigid binder is sodium carboxymethyl cellulose, and the conductive agent is conductive carbon black; the mass ratio of the negative electrode main material, the rigid binder and the conductive agent is 18.86-943:0.3-15:0.14-7.
2. The method for improving the efficiency of dry pulping process of sodium ion negative electrode according to claim 1, characterized in that: The conductive additive comprises carbon nanotubes or modified carbon nanotubes; the modified carbon nanotubes have morpholine groups, pyridine groups and polyethylene glycol groups.
3. The method for improving the efficiency of dry pulping process of sodium ion negative electrode according to claim 1, characterized in that: The dispersant is N-methylpyrrolidone, and the mass ratio of the negative electrode main material to the dispersant is 18.86-943:0.1886-9.
43.
4. The method for improving the efficiency of dry pulping process of sodium ion negative electrode according to claim 1, characterized in that: The mass ratio of the negative electrode main material to the conductive additive is 18.86-943:0.1-5.
5. The method for improving the efficiency of dry pulping process of sodium ion negative electrode according to claim 1, characterized in that: The elastic binder is styrene-butadiene rubber, and the mass ratio of the negative electrode main material to the elastic binder is 18.86-943:0.6-30.
6. The method for improving the efficiency of dry pulping process of sodium ion negative electrode according to claim 2, characterized in that: The modified carbon nanotubes are obtained by modifying carboxylated carbon nanotubes with N-(2-hydroxyethyl)morpholine, N-(2-hydroxyethyl)-3-pyridinecarboxamide and polyethylene glycol.
7. A method for improving the efficiency of dry pulping process of sodium ion negative electrode according to claim 6, characterized in that: The mass ratio of the N-(2-hydroxyethyl)morpholine to the carboxylated carbon nanotubes is 0.1-2:0.075-1.5; or, the mass ratio of the N-(2-hydroxyethyl)-3-pyridinecarboxamide to the carboxylated carbon nanotubes is 0.075-1.5:0.075-1.5; or, the mass ratio of the polyethylene glycol to the carboxylated carbon nanotubes is 0.125-2.5:0.075-1.
5.
8. The sodium ion negative electrode slurry prepared by the method according to any one of claims 1 to 7.
9. A negative electrode sheet obtained by coating the sodium ion negative electrode slurry according to claim 8 on a copper foil current collector.
Citation Information
Cited By
Preparation process of lithium iron phosphate positive pole piece
CN120854485A